Neuroendocrine carcinoma of the nasopharynx - a case report. - Subha, Sethu Thakachy (Prague Development Center, 2011)

(untitled)
Small cell neuroendocrine carcinoma, also known as oat cell carcinoma is a frequently encountered bronchogenic neoplasm. Neuroendocrine carcinomas of the head and neck are rare aggressive tumors and pose a diagnostic and management challenge. Differentiation from conventional nasopharyngeal carcinoma is difficult due to morphological characteristics and small biopsy specimen. Distinguishing is very important because of difference in natural history ,prognosis and treatment among these neoplasms. In this article we present an unusual case of 51 year old man with small cell neuroendocrine carcinoma of nasopharynx, who was treated with radiotherapy and achieved complete tumor remission. Subsequently he developed local recurrence and liver metastasis and succumbed to the disease.